2017
DOI: 10.21577/0103-5053.20170171
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Binding Analysis of Flavonoids with Alpha-Amylase Inhibitory Activity from Lotus Leaf

Abstract: Lotus leaf is gaining growing popularity due to its various benefits and widely usage. In this paper, ten flavonoids in lotus leaf extract were analyzed by high performance liquid chromatography (HPLC). Centrifugal ultrafiltration combined liquid chromatography was used to screen alphaamylase inhibitors from ten flavonoids mixture and the binding degrees ranged from 2.34 to 94.1%. The alpha-amylase inhibition and the 1,1-diphenyl-2-picrylhydrazyl (DPPH) antioxidant activity of ten flavonoids were verified as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…In addition, the flowers exhibited the weakest inhibitory activities (IC 50 : 4.94 mg/mL for amylase and 1.41 mg/mL for tyrosinase). The findings could be related with chemical profiles of the tested extracts and some compounds in extracts such as hyperoside [ 70 , 71 ], ferulic acid [ 72 , 73 ], and apigenin [ 74 , 75 ] have been reported as inhibitory agents in earlier studies. A moderate positive correlation was also observed between total phenolic content and the enzyme inhibitory abilities Table 4 .…”
Section: Resultsmentioning
confidence: 88%
“…In addition, the flowers exhibited the weakest inhibitory activities (IC 50 : 4.94 mg/mL for amylase and 1.41 mg/mL for tyrosinase). The findings could be related with chemical profiles of the tested extracts and some compounds in extracts such as hyperoside [ 70 , 71 ], ferulic acid [ 72 , 73 ], and apigenin [ 74 , 75 ] have been reported as inhibitory agents in earlier studies. A moderate positive correlation was also observed between total phenolic content and the enzyme inhibitory abilities Table 4 .…”
Section: Resultsmentioning
confidence: 88%
“…Also, it was mentioned that its combination with acarbose showed a great synergic capacity to inhibit α -amylase and glucosidase [ 44 ]. It was recorded that kaempferol, a flavonoid present in the ethanolic fraction by 0.032 mg/100 g of DW, showed a higher inhibition capacity of α -amylase and this could be due to their high binding to the pancreatic enzyme [ 45 ]. Also, catechin, a molecule present with an important quantity in EtOH (89.03) followed by MeOH fraction (19.92), showed its capacity to inhibit the pancreatic α -amylase [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Wang et al demonstrated that N. nucifera leaf flavonoids could prevent diabetes type 2 through the inhibition of α-amylase [51]. In the same way, Liao et al analyzed the binding affinity of ten flavonoids from N. nucifera leaf on α-amylase using spectroscopic methods [52]. They found that, among the tested flavonoids, Kae, Api and Iso displayed the most potent inhibiting potential on α-amylase activity.…”
Section: Flavonoids From N Nucifera and Their Pharmacological Actmentioning
confidence: 99%
“…They found that, among the tested flavonoids, Kae, Api and Iso displayed the most potent inhibiting potential on α-amylase activity. Their structure–function experiments also showed that the hydrogenation of the C 2 =C 3 double bond of the flavonoid backbone of Quer and Api as well as the hydroxylation of 3 and 3′ positions decreased the affinity of the flavonoids for this enzyme [52]. Additionally, the methanol extract from seed epicarp of N. nucifera revealed the significant α-amylase inhibiting activity, and was suggested to develop as potential anti-diabetic agents [49].…”
Section: Flavonoids From N Nucifera and Their Pharmacological Actmentioning
confidence: 99%